(untitled) (Maryland, US., 1990)
Sympopium 7: Proceeding from the International Symposium and Educational Workshop on Fish-marking Techniques, held in Seattle, WA, June 1988 Landmark coverage of external, internal, electronic, genetic, and chemical tags and marks, with emphasis on methodology, tag evaluation, data analysis, and program applications. This book is intended for fish ecologists, researchers, stock assessment biologists, and fisheries managers.
Keywords: Fish tagging